Emerging Trends of the Applications of Nanoparticles in Dentistry: A Literature Review : Applications of Nanoparticles in Dentistry - Armanfar, Maryam; Abbasi, Farid (Journal of Dental School, 2021)
Objectives Microorganisms are the main culprits responsible for many oral conditions including dental caries and periodontal diseases. To increase the quality of dental treatments, we can produce dental materials with antimicrobial properties. Nanoparticles with their antimicrobial activities can help achieve this goal. The purpose of this study was to describe the applications of nanoparticles in different fields of dentistry. Methods An electronic search was conducted in the PubMed and Google Scholar to find articles related to the applications of nanoparticles in dentistry. No limitations were set regarding the date of publication or the language. We selected 73 articles and summed up the information. Results Nanoparticles can be effectively used in various fields of dentistry including prosthodontics, oral medicine, periodontics, implant therapy, bone augmentation, restorative and preventive dentistry, orthodontics and endodontics, as well as in dental office disinfectants. Conclusion Incorporating nanoparticles into dental materials is the most common application of nanoparticles in dentistry, which leads to an increase in antimicrobial properties of dental materials. Cancer diagnosis and treatment, regeneration of alveolar bone defects, and treatment of tooth hypersensitivity are the other emerging applications of nanoparticles in dentistry.